Formal synthesis of (-) anisomycin via organocatalysis - Chouthaiwale, Pandurang V.; Kotkar, Shriram P.; Sudalai, Arumugam (Arkivoc, 2009)
An efficient formal synthesis of (-) anisomycin (1), a potent antibiotic agent, has been achieved in good yields and excellent diastereoselectivity. The key steps are proline-catalyzed sequential alpha-amination or alpha-aminoxylation of aldehyde 2 followed by tandem Horner-Wadsworth-Emmons olefination.
Keywords: alpha-Amination; alpha-aminoxylation; anisomycin; olefination; Proline